Early Life Stress Induces Different Behaviors in Adolescence and Adulthood May Related With Abnormal Medial Prefrontal Cortex Excitation/Inhibition Balance - Chen, Yiwen; Zheng, Yuanjia; Yan, Jinglan; Zhu, Chuanan; Zeng, Xuan; Zheng, Shaoyi; Li, Wenwen; Yao, Lin; Xia, Yucen; Su, Wei-wei; Chen, Yongjun (Frontiers in Neuroscience, 2022)
Early life stress is thought to be a risk factor for emotional disorders, particularly depression and anxiety. Although the excitation/inhibition (E/I) imbalance has been implicated in neuropsychiatric disorders, whether early life stress affects the E/I balance in the medial prefrontal cortex at various developmental stages is unclear. In this study, rats exposed to maternal separation (MS) that exhibited a well-established early life stress paradigm were used to evaluate the E/I balance in adolescence (postnatal day P43–60) and adulthood (P82–100) by behavior tests, whole-cell recordings, and microdialysis coupled with high performance liquid chromatography-mass spectrometry (HPLC-MS) analysis. First, the behavioral tests revealed that MS induced both anxiety- and depressive-like behaviors in adolescent rats but only depressive-like behavior in adult rats. Second, MS increased the action potential frequency and E/I balance of synaptic transmission onto L5 pyramidal neurons in the prelimbic (PrL) brain region of adolescent rats while decreasing the action potential frequency and E/I balance in adult rats. Finally, MS increases extracellular glutamate levels and decreased the paired-pulse ratio of evoked excitatory postsynaptic currents (EPSCs) of pyramidal neurons in the PrL of adolescent rats. In contrast, MS decreased extracellular glutamate levels and increased the paired-pulse ratio of evoked EPSCs of pyramidal neurons in the PrL of adult rats. The present results reveal a key role of E/I balance in different MS-induced disorders may related to the altered probability of presynaptic glutamate release at different developmental stages.